(untitled) (Bangladesh Journal of Pharmacology, 2025)
This study investigated the effects of astragalus polysaccharides on prolifer-ation, apoptosis, migration, invasion, and epidermal growth factor receptor (EGFR)/mitogen-activated protein kinase (MAPK) signaling pathway in human rheumatoid arthritis fibroblast-like synoviocytes (MH7A cells). MH7A cells were randomly divided into control, lipopolysaccharide (LPS), and astragalus polysaccharides (50, 100, and 200 μg/mL) groups for experimental investigation. Cell viability significantly decreased when the concentration of Astragalus polysaccharides exceeded 200 µg/ML; therefore, a dose ≤200 µg/mL was selected for subsequent experiments (p<0.05). Compared with the LPS group, astragalus polysaccharides groups showed reduced cell viability, increased apoptosis rates, and decreased migration and invasion rates (all p<0.05). Furthermore, EGFR expression and the relative expression of p-P38MAPK/P38MAPK were both reduced (both p<0.05). In conclusion, astragalus polysaccharides may inhibit LPS-induced proliferation, migration, and invasion of fibroblast-like synoviocytes by suppressing the EGFR/MAPK signaling pathway, while promoting apoptosis.